2018
DOI: 10.1055/s-0038-1623512
|View full text |Cite
|
Sign up to set email alerts
|

Does Knowing Someone with Breast Cancer Influence the Prevalence of Adherence to Breast and Cervical Cancer Screening?

Abstract: There was high adherence to the recommended screening practices; knowing someone with breast cancer might make women more sensitive to this issue as they were more likely to undergo methods which are not recommended for the screening of the general population, such as breast ultrasound and specialist consultation; family history is possibly an additional cause of concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In line with this study, a Saudi study found that knowing someone who has BC is a significant predictor of having good knowledge of BSE [ 35 ]. Furthermore, these findings were supported by a study from Brazil, which found that knowing someone with BC had a significant influence on adherence to BSE [ 36 ]. These similarities across the different studies stem from an increased interest in understanding BSE as a result of the experience with the severity of BC.…”
Section: Discussionmentioning
confidence: 56%
“…In line with this study, a Saudi study found that knowing someone who has BC is a significant predictor of having good knowledge of BSE [ 35 ]. Furthermore, these findings were supported by a study from Brazil, which found that knowing someone with BC had a significant influence on adherence to BSE [ 36 ]. These similarities across the different studies stem from an increased interest in understanding BSE as a result of the experience with the severity of BC.…”
Section: Discussionmentioning
confidence: 56%
“…This finding is consistent with the observation of a heightened knowledge of a certain cancer when reported among a person's social network, which personalizes the cancer for them. 49,50 Finally, persons may have heard about treatment options for anal cancer, which may have negative associations, further heightening level of worry. 28…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the observation of a heightened knowledge of a certain cancer when reported among a person's social network, which personalizes the cancer for them. 49,50 Finally, persons may have heard about treatment options for anal cancer, which may have negative associations, further heightening level of worry. 28 The level of worry is a perceived expression that varies with individual personality types and may be subject to behavioral factors that our study was not powered to measure.…”
Section: Discussionmentioning
confidence: 99%
“…entrevistaram 467 mulheres americanas onde mulheres com histórico familiar de câncer de mama são 2,5 vezes prováveis de realizarem a mamografia 23 . Além disso, um estudo realizado em Minas Gerais concluiu que conhecer alguém com câncer de mama também influência na decisão de realizar a prevenção secundária 24 . O seio é um símbolo da feminilidade das mulheres, com isso, conhecer alguém com câncer de mama poderia sensibilizar as mulheres nesse assunto resultando em um maior autocuidado feminino.…”
Section: Discussionunclassified